2013
DOI: 10.1038/jp.2013.54
|View full text |Cite
|
Sign up to set email alerts
|

Effect of position of infant during phototherapy in management of hyperbilirubinemia in late preterm and term neonates: a randomized controlled trial

Abstract: Nursing babies in supine position when compared with periodic position change during phototherapy does not decrease the duration of phototherapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
23
0

Year Published

2014
2014
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(24 citation statements)
references
References 15 publications
1
23
0
Order By: Relevance
“…But rotating the infant from prone to supine or supine to prone (thus exposing unblanched skin to the light) had no effect on the rate at which the bilirubin level was lowered. These observations confirm the data from 3 studies (25)(26)(27) all of which demonstrated that turning the infant does not improve the efficacy of phototherapy. Thus, while phototherapy certainly decreases the bilirubin in the skin and subcutaneous tissues, this effect cannot be responsible for the ability of phototherapy to decrease the bilirubin in the plasma.…”
Section: Changing the Position Of The Infant And Where Photo-therapysupporting
confidence: 89%
“…But rotating the infant from prone to supine or supine to prone (thus exposing unblanched skin to the light) had no effect on the rate at which the bilirubin level was lowered. These observations confirm the data from 3 studies (25)(26)(27) all of which demonstrated that turning the infant does not improve the efficacy of phototherapy. Thus, while phototherapy certainly decreases the bilirubin in the skin and subcutaneous tissues, this effect cannot be responsible for the ability of phototherapy to decrease the bilirubin in the plasma.…”
Section: Changing the Position Of The Infant And Where Photo-therapysupporting
confidence: 89%
“…Having said so, Bhethanabhotla et al . () did generally explain in their report concerning blinding:
Owing to obvious nature of intervention, blinding was not possible in our study. (Bhethanabhotla et al .
…”
Section: Resultsmentioning
confidence: 73%
“…Amid the five studies, one (Bhethanabhotla et al . ) evidently analysed the key outcome of all subjects initially allocated to groups. There was no loss of follow up.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Pursuant to this understanding, infants in phototherapy were routinely alternated from prone to supine position to increase the efficacy of phototherapy (12). However, this routine was largely discontinued when it was found that the efficacy of phototherapy is independent of alternating the position of the infant (10,(13)(14)(15). Other observations also support the hypothesis that the effect of phototherapy is predominantly intravascular.…”
Section: Discussionmentioning
confidence: 99%